Structural studies of a fucogalactoxyloglucan from pinus radiata primary cell walls : a thesis presented in partial fulfilment of the requirements for the degree of Master of Science in Biochemistry at Massey University - Little, John William Lester (Massey University, 1980)
1. The changes in carbohydrate composition of elongating Pinus radiata primary cell walls were investigated. In the hemicellulose B extracts, a large increase in the percentage of non-starch, non-cellulosic, glucose was found to occur on cessation of cell-wall elongation. 2. By fractionation of the hemicellulose B extracts, with a variety of methods involving precipitation from an aqueous solution, a xyloglucan was purified. This xyloglucan was the major hemicellulose of the Pinus radiata hypocotyl cell wall. 3. Characterisation studies on the xyloglucan involved: quantitative analysis of the monosaccharides derived by nitric acid/urea hydrolysis; identification of the partial hydrolysis products derived by trifluoroacetic acid hydrolysis; quantitation of the sugar linkages using methylation by the Hakomori method; and analysis of the anomeric configuration of component sugars using chromium trioxide oxidation. 4. From the results a tentative structure has been suggested for the xyloglucan, consisting of a backbone of B-D-gluco-pyranose residues linked together by 1-4 glycosidic bonds, and with sidechains of single xylose residues linked through C-6 of the glucose units. Galacto and fuco-1,2- galacto sidechains are attached to some of the xylose residues, probably through the C-2 of the xylose.
Keywords: Pinus radiata; Plant cell walls; Wood Anatomy